Respuesta :
we have
case a) [tex] |6| [/tex]
[tex] |6|=6 [/tex]
therefore
the expression is equal to [tex] 6 [/tex]
case b) [tex] |-6| [/tex]
[tex] |-6|=6 [/tex]
therefore
the expression is equal to [tex] 6 [/tex]
case c) [tex] -|6| [/tex]
[tex] -|6|=-6 [/tex]
therefore
the expression is not equal to [tex] 6 [/tex]
case d) [tex] -|-6| [/tex]
[tex] -|-6|=-6 [/tex]
therefore
the expression is not equal to [tex] 6 [/tex]
case e) [tex] |0-6| [/tex]
[tex] |0-6|=|-6|=6 [/tex]
therefore
the expression is equal to [tex] 6 [/tex]
case f) [tex] |-2|*|3| [/tex]
[tex] |-2|*|3|=2*3=6 [/tex]
therefore
the expression is equal to [tex] 6 [/tex]
therefore
the answer is
The expressions that are equal to [tex] 6 [/tex] are
[tex] |6| [/tex]
[tex] |-6| [/tex]
[tex] |0-6| [/tex]
[tex] |-2|*|3| [/tex]